Determinants of Takaful Performance in Malaysia - Sahudin, Zahariah; Abdullah, Hasni; Abdul Rahim, Husniyah; Bahrudin, Nur Zahidah; Pardi, Faridah (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S2 (2022): Theme: Digitalization Progress in Business Practices, 2022)
This paper intends to find out the factors influencing the company’s performance in Takaful industry in Malaysia. It is done by investigating on the micro level factors such as liquidity and firm size. For macro level factors, the study employs inflation and gross domestic product to know their influence towards performance of Takaful companies. The data for this research were gathered from the annual report of the company itself and from the World Bank website. The duration of the study is from year 2011 until 2020. The sample size of the study is five Takaful companies, and it makes the observations become 50. Panel Data Analysis is used to analyse the data. As a result, it shows that liquidity, size of the firm and GDP have significant relationship with the performance of Takaful companies in Malaysia. It is hope that the findings from this study will give impact and contribution towards the existing body of knowledge. Furthermore, it will give better understanding to the managerial level in order for them to improve their firm’s performance, thus will improve takaful industry performance in Malaysia. Research paper Keywords: Takaful performance, return on asset, size of the firm, liquidity, GDP Reference to this paper should be made as follows: Sahudin, Z., Abdullah, H., Abdul Rahim, H., Bahrudin, N. Z., & Pardi, F. (2022). Determinants of Takaful Performance in Malaysia. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 1–17.